2023
DOI: 10.1038/s41598-023-27836-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of Lavatera thuringiaca L. biomass ash after pre-sowing stimulation of seeds with He–Ne laser light

Abstract: The article presents the effect of pre-sowing Lavatera thuringiaca L. seeds stimulation with He–Ne laser light on the chemical composition (P, S, K, Ca, Mn, Fe, Ni, Cu and Zn content) of ash obtained after combustion of shoots of different ages. Results varied, but it was confirmed that pre-sowing exposure of seeds to this physical factor for 10-min has the most pronounced effect on K, Cu and Mn content increase (6%, 20%, 31% increase respectively) in the ash after the first year of vegetation as well as on Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…In order to improve the seed quality, physical factors such as electric, laser, and magnetic fields or plasma are also used. Studies found that the exposure of L. thuringiaca seeds to He-Ne laser light had a beneficial effect on field emergence capacity and biometric characteristics (Budzeń et al, 2015), seed germination (Budzeń et al, 2018), and the chemical composition of biomass ash (Budzeń et al, 2023). Pawlat et al (2017) proved that pre-sowing plasma stimulation of seeds improved germination parameters, such as germination capacity and germination energy.…”
Section: Botanical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the seed quality, physical factors such as electric, laser, and magnetic fields or plasma are also used. Studies found that the exposure of L. thuringiaca seeds to He-Ne laser light had a beneficial effect on field emergence capacity and biometric characteristics (Budzeń et al, 2015), seed germination (Budzeń et al, 2018), and the chemical composition of biomass ash (Budzeń et al, 2023). Pawlat et al (2017) proved that pre-sowing plasma stimulation of seeds improved germination parameters, such as germination capacity and germination energy.…”
Section: Botanical Characteristicsmentioning
confidence: 99%
“…As shown by Budzeń et al (2016Budzeń et al ( , 2021, the application of pre-sowing He-Ne laser light stimulation influences the energy parameters of L. thuringiaca biomass, namely it increased the heat of combustion and the calorific value of the grown shoots. Besides, an innovative method for improvement of the chemical composition of L. thuringiaca biomass ash was presented by these authors (Budzeń et al, 2023). ey determined the effect of pre-sowing seed stimulation with He-Ne laser light on the chemical composition (P, S, K, Ca, Mn, Fe, Ni, Cu, and Zn content) of ash.…”
Section: Raw Materials For Energy Purposesmentioning
confidence: 99%